Engineering secure software and systems : 9th International Symposium, ESSoS 2017, Bonn, Germany, July 3-5, 2017, Proceedings /: 9th International Symposium, ESSoS 2017, Bonn, Germany, July 3-5, 2017, Proceedings. (2017) - Unknown
No abstract available